Regulation of Toll and Toll-like receptor signaling by the endocytic pathway - Lund, Viktor K (Landes Bioscience, 2011)
The Toll/TLR receptor family plays a central role in both vertebrate and insect immunity, driving the activation of humoral immunity in response to pathogens. In Drosophila, Toll is also responsible for directing the formation of the Dorsal/NFkappaB gradient specifying dorsoventral patterning of the embryo. Two recent studies have revealed that endocytosis and elements of the molecular machinery governing endosomal progression are required for Drosophila Toll signaling in development and immunity. We demonstrated that Toll is not only present at the plasma membrane but also in a Rab5(+) early endosomal compartment in the embryo and that the distribution of constitutively active Toll(10B) is shifted towards endosomes. Localized inhibition of Rab5 function on the ventral side leads to a reduction of nuclear Dorsal levels, while locally increasing Rab5 function leads to potentiation of signaling. Independently, another laboratory identified the endosomal protein Mop as a potentiator of Toll signaling in Drosophila cell culture and fat-body tissue. Mop functions together with the ESCRT 0 component, Hrs, previously reported to stimulate endosomal progression and the signaling ability of internalized EGFR. We discuss these studies and briefly summarize the most significant findings concerning the role of intracellular localization and trafficking in mammalian TLR function.